Human Amniotic Fluid Mesenchymal Stem Cells from Second- and Third-Trimester Amniocentesis: Differentiation Potential, Molecular Signature, and Proteome Analysis - Jurate Savickiene; Grazina Treigyte; Sandra Baronaite; Giedre Valiuliene; Algirdas Kaupinis; Mindaugas Valius; Audrone Arlauskiene; Ruta Navakauskiene (Stem Cells International)
Human amniotic fluid stem cells have become an attractive stem cell source for potential applications in regenerative medicine and tissue engineering. The aim of this study was to characterize amniotic fluid-derived mesenchymal stem cells (AF-MSCs) from second- and third-trimester of gestation. Using two-stage protocol, MSCs were successfully cultured and exhibited typical stem cell morphological, specific cell surface, and pluripotency markers characteristics. AF-MSCs differentiated into adipocytes, osteocytes, chondrocytes, myocytes, and neuronal cells, as determined by morphological changes, cell staining, and RT-qPCR showing the tissue-specific gene presence for differentiated cell lineages. Using SYNAPT G2 High Definition Mass Spectrometry technique approach, we performed for the first time the comparative proteomic analysis between undifferentiated AF-MSCs from late trimester of gestation and differentiated into myogenic, adipogenic, osteogenic, and neurogenic lineages. The analysis of the functional and expression patterns of 250 high abundance proteins selected from more than 1400 demonstrated the similar proteome of cultured and differentiated AF-MSCs but the unique changes in their expression profile during cell differentiation that may help the identification of key markers in differentiated cells. Our results provide evidence that human amniotic fluid of second- and third-trimester contains stem cells with multilineage potential and may be attractive source for clinical applications.